2-Absorbing δ-Primary Intuitionistic Fuzzy Ideals of Commutative Rings - Onar, Serkan; Ozkan, Erdogan Mehmet; Ersoy, Bayram Ali; Hila, Kostaq (WORLD SCIENTIFIC PUBL CO PTE LTD, 2023)
In this paper, we study the primary intuitionistic fuzzy ideal, the intuitionistic fuzzy ideal expansion and delta-primary intuitionistic fuzzy ideal which assemble prime intuitionistic fuzzy ideals and primary intuitionistic fuzzy ideals. Some properties of them are investigated. Also, we scrutinize the relationships of delta-primary intuitionistic fuzzy ideal and delta-primary ideal of a commutative ring R. Moreover, we give a fundamental result about correspondence theorem for delta-primary intuitionistic fuzzy ideals. Further, we introduce 2-absorbing delta-primary intuitionistic fuzzy ideals which are the generalization of 2absorbing intuitionistic fuzzy ideals and 2-absorbing primary intuitionistic fuzzy ideals. Some properties of them are obtained.
Keywords: 2-absorbing intuitionistic fuzzy ideals; 2-absorbing delta-primary intuitionistic fuzzy ideals; OPERATIONS; Mathematics